Designing an Information System for Recording Incoming and Outgoing Goods at the Warehouse of the Engineering Faculty, Universitas Sebelas Maret, Surakarta: Perancangan Sistem Informasi Pencatatan Barang Masuk Dan Barang Keluar Pada Gudang Fakultas Teknik Universitas Sebelas Maret Surakarta - Mudakir, Mudakir; Naury, Chairullah; Santosa, Eka Budhi (Politeknik Harapan Bangsa Surakarta, 2023)
The Faculty of Engineering, Universitas Sebelas Maret (UNS) in service activities for students requires consumables stored in the warehouse of the Faculty of Engineering, UNS. Every month a document recapitulation is carried out to control the circulation that occurs in the warehouse of the UNS Faculty of Engineering. The document recap system still uses the manual method, namely by recording incoming and outgoing goods to the ledger. Data from the general ledger is copied into the Microsoft Excel application to create a circulation report. The current manual system still has human errors that often occur, such as missing or tucked records of incoming and outgoing goods. This has an impact on when recapitulating the results of the information data obtained is less accurate. Based on the description of the background above, it can be formulated the problem to be solved in this study is